2010
DOI: 10.1007/s10943-010-9428-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Imams in American Muslim Health: Perspectives of Muslim Community Leaders in Southeast Michigan

Abstract: American Muslims are a diverse and growing population, numbering nearly 200,000 in Southeast Michigan. Little empirical work exists on the influence of Islam upon the healthcare behaviors of American Muslims, and there is to date limited research on the roles that imams, Muslim religious leaders, play in the health of this community. Utilizing a community-based participatory research (CBPR) model through collaboration with four key community organizations, we conducted semi-structured interviews with 12 commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 31 publications
3
68
0
Order By: Relevance
“…Imams may play an important role in providing health promotion messages to their community, including the value of undertaking preventive screenings and treatment [29, 30]. In this research, messages shared by an Imam were seen to be acceptable and influential because they were being delivered by a faith leader.…”
Section: Discussionmentioning
confidence: 89%
“…Imams may play an important role in providing health promotion messages to their community, including the value of undertaking preventive screenings and treatment [29, 30]. In this research, messages shared by an Imam were seen to be acceptable and influential because they were being delivered by a faith leader.…”
Section: Discussionmentioning
confidence: 89%
“…22 Additionally, the local Somali community has a strong oral tradition used to inform and advise one another.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies discussed Muslim patients' preferences of seeking help from a therapist at least familiar with their traditions if not Muslim as well. Another study exploring the role of imams in the mental health of American Muslims (Padela, Killawi, Heisler, Demonner, & Fetters, 2011) found that imams have a role in framing health information for congregants as well as in health care settings for non-Muslim practitioners. The work of Ali and Milstein (2012) also brings forward the roles of imams in referring congregants to clinicians, while continuing their own counseling, to provide a collaborative, culturally sensitive approach to mental health.…”
mentioning
confidence: 99%